Interdisciplinary methodological framework of biomechanics and occupational psychology for MSD prevention - Adriana Savescu; Pascal Simonet; Clarisse Gaudez; Gabriel Fernandez (Activités)
In France and globally, musculoskeletal disorders (MSD) remain the most widespread occupational diseases. The scientific literature has established that links exist between occurrence of MSD and the professional gesture. The aim of this paper is to analyse how an intervention was conducted within the general methodological framework of occupational psychology using activity clinical research based on professional gesture analysis and it has enjoyed interdisciplinary co-operation with biomechanics. The interdisciplinary methodology implemented with eight gravediggers was based on different steps including a detailed analysis of the muscular activity of the shoulder and back muscles. The results show that the presented methodology allows opening more widely the potential development zone of the gesture in the gravediggers' activity by stimulating their professional discussions. The visibility and discussion in the profession of inter- and intra-individual variability has opened up the professional world to new forms of MSD prevention actions.